Mouse Population-Based Approaches to Investigate Adverse Drug Reactions - Mosedale, Merrie (Drug metabolism and disposition, 2018)
Genetic variation is now recognized as a key factor in the toxicity of pharmaceutical agents. However, genetic diversity is not present in standard nonclinical toxicology models, and small clinical studies (phase I/II) may not include enough subjects to identify toxicity liabilities associated with less common susceptibility factors. As a result, many drugs pass through preclinical and early clinical studies before safety concerns are realized. Furthermore, when adverse drug reactions are idiosyncratic in nature, suggesting a role for rare genetic variants in the toxicity susceptibility, even large clinical studies (phase III) are often underpowered (due to low population frequency and/or small effect size of the risk factor) to identify associations that may be used for precision medicine risk mitigation strategies. Genetically diverse mouse populations can be used to help overcome the limitations of standard nonclinical and clinical studies and to model toxicity responses that require genetic susceptibility factors. Furthermore, mouse population-based approaches can be used to: 1) identify sensitive strains that can serve as a screening tool for next-in-class compounds, 2) identify genetic susceptibility factors that can be used for risk mitigation strategies, and 3) study mechanisms underlying drug toxicity. This review describes genetically diverse mouse populations and provides examples of their utility in investigating adverse drug response. It also explores recent efforts to adapt mouse population-based approaches to in vitro platforms, thereby enabling the incorporation of genetic diversity and the identification of genetic risk factors and mechanisms associated with drug toxicity susceptibility at all stages of drug development.